Russian Federation : Financial Sector Assessment Program: Technical Note-Macroprudential Policy. (IMF Staff Country Reports; Country Report ;, 2016)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for the Russian Federation in the area of macroprudential policy. Financial stability oversight responsibilities are currently shared between the Central Bank of Russia (CBR) and the high-level interagency National Council on Ensuring Financial Stability. In recent years, the CBR has used a number of macroprudential tools to deal with risks, mainly those stemming from retail lending. The CBR has tightened provisioning requirements and increased capital risk weights to curb excessive growth of unsecured consumer lending, which has helped banks better handle credit risk that materialized. However, the CBR law should be amended to provide for a more comprehensive set of macroprudential tools.